Evaluation of Minimum Required Safe Distance between Two Consecutive Dental Chairs for Optimal Asepsis - Chiramana, Sandeep; Bindu O, Swetha Hima; Kadiyala, Krishna Kishore; Prakash, Manne; Prasad, Tadi Durga; Chaitanya, S Krishna (Journal of Orofacial Research, 2013)
Cross infection and self-protection, these two words are like a lurid to the health care professionals. A balance has to be maintained among those two words if not, it’s after affects are unpredictable. It is believed that even after following the code of practice, some elements such as the aerosols that are evolved during the use of high speed rotary instruments such as airotor and scaler are difficult to handle. Aerosols containing microbes from oral cavity of the patient are a risky source of infection. The best way to fight against these aerosols is to keep a distance from them. But it is not known how far these airborne microorganisms spread under various clinical environments. This article emphasizes the safe distance that has to be maintained around each dental chair to prevent cross contamination.